Towards Autonomous Robotic Systems 12th Annual Conference, TAROS 2011, Sheffield, UK, August 31 -- September 2, 2011, Proceedings - Groß, Roderich.; Groß, Roderich.; Alboul, Lyuba.; Alboul, Lyuba.; Melhuish, Chris.; Melhuish, Chris.; Witkowski, Mark.; Witkowski, Mark.; Prescott, Tony T.; Prescott, Tony T.; Penders, Jacques.; Penders, Jacques. (Lecture Notes in Artificial Intelligence ;, 2011)
This book constitutes the refereed proceedings of the 12th Annual Conference Towards Autonomous Robotics Systems, TAROS 2011, held in Sheffield, UK, in August/September 2011. The 32 revised full papers presented together with 29 two-page abstracts were carefully reviewed and selected from 94 submissions. Among the topics addressed are robot navigation, robot learning, human-robot interaction, robot control, mobile robots, reinforcement learning, robot vehicles, swarm robotic systems, etc.